Early gene expression changes by Epstein‐Barr virus infection of B‐cells indicate CDKs and survivin as therapeutic targets for post‐transplant lymphoproliferative diseases. Issue 10 (29th May 2013) - Bernasconi, Michele; Ueda, Seigo; Krukowski, Patricia; Bornhauser, Beat C.; Ladell, Kristin; Dorner, Marcus; Sigrist, Juerg A.; Campidelli, Cristina; Aslandogmus, Roberta; Alessi, Davide; Berger, Christoph; Pileri, Stefano A.; et al.
Abstract : Lymphoproliferative diseases (LPDs) associated with Epstein‐Barr virus (EBV) infection cause significant morbidity and mortality in bone marrow and solid organ transplant recipients. To gain insight into LPD pathogenesis and to identify potential effective therapeutic approaches, we investigated early molecular events leading to B‐cell transformation by gene expression profiling of EBV‐infected B‐cells from tonsils by Affymetrix microarray 72 hr postinfection when the B‐cells hyperproliferation phase starts. Cell cycle and apoptosis were the most significantly affected pathways and enriched gene sets. In particular, we found significantly increased expression of cyclin‐dependent kinase (CDK)1 and CCNB1 (cyclin B1) and of one of their downstream targets BIRC5 (survivin). Importantly, the strong upregulation of the antiapoptotic protein survivin was confirmed in lymphoblastoid cell lines (LCLs) and 71% of EBV‐positive post‐transplant EBV‐LPD lesions scored positive for survivin. The validity of early transforming events for the identification of therapeutic targets for EBV‐LPD was confirmed by the marked antiproliferative effect of the CDK inhibitor flavopiridol on LCLs and by the strong induction of apoptosis by survivin inhibition with YM155 or terameprocol. Our results suggest that targeting of CDKs and/or survivin in post‐transplant EBV‐LPD by specific inhibitors might be an important approach to control and eliminate EBV‐transformed B‐cells that should be further considered. Abstract : What's new? Lymphoproliferative diseases associated with Epstein‐Barr virus (EBV) infection cause morbidity and mortality in bone marrow and solid organ transplant recipients. Here the authors analyzed the early molecular events leading to B‐cell transformation following EBV infection. They demonstrated in vitro, 72 hours post‐infection when B‐cell hyperproliferation starts, the up‐regulation of cell cycle‐related genes (CDKs) and of the apoptosis inhibitor survivin. Treatment with specific CDK or survivin inhibitors led to EBV‐transformed B‐cell death. Importantly, survivin over‐expression was also found in EBV‐positive post‐transplant diffuse large B‐cell lymphomas, suggesting that inhibition of CDKs or survivin could represent a potential therapy for EBV‐associated lymphoproliferative diseases.